KARAKTERISTIK DAN KEBUTUHAN PARKIR MOBIL DI KAMPUS TERPADU UNIVERSITAS ISLAM INDONESIA - Prima Juanita Romadhona; Muhammad Rizki Ramadhan (Asian Journal of Innovation and Entrepreneurship, 2017)
Universitas Islam Indonesia is private university with the biggest faculty number in Indonesia. Physically, the building has expansion rapidly as much as the academic facilities. The improvement of student number means problems in the parking lot. The purpose of this study was to analyze the characteristics of parking and parking space requirements for the existing and five years later. Primary data obtained by direct observation such as entry and exit of vehicles parking areas and parking facilities inventory. From the analysis of parking index, it shows that 3 parking locations are no longer able to accommodate the needs at FIAI, FTSP Lecturer and FPSB-Rector. Appropriate parking needs of students are 269 SRP. According to the Ministry of Transportation requires 4812.95 m2, which means it meets the UII parking lot of existing condition. However, for the next 5 years it needs 443 SRP which means the existing parking lot cannot meets the requirements.